Patient and Public Involvement and Engagement in a doctoral research project exploring self‐harm in older adults. (26th May 2019) - Troya, M. Isabela; Chew‐Graham, Carolyn A.; Babatunde, Opeyemi; Bartlam, Bernadette; Higginbottom, Adele; Dikomitis, Lisa
Abstract: Background: The contribution of involving patients and public in health research is widely reported, particularly within mental health research. Less is written about such contributions to doctoral research. The research focus of this doctoral research, self‐harm in older adults, was put forward by a Patient Public Involvement Engagement (PPIE) group, who contributed to its development. Aims: Critically reflect on the process, potential impact and identify challenges and opportunities in involving robust PPIE in a doctoral study. Methods: Three PPIE members contributed to a systematic review (SR) and a qualitative study through a series of four workshops to meet the aims of the study. PPIE contributed to developing the SR review questions, protocol, data analysis and dissemination of findings. For the qualitative study, they helped develop research questions, protocol, public‐facing documentation, recruitment strategies and data analysis. Involvement followed the GRIPP2‐SF reporting checklist. Results: PPIE enhanced methodological rigour, data analysis, interpretation and dissemination of findings. Challenges included lack of ethical guidance, time‐related pressures and ensuring support for PPIE members. These were successfully managed through ongoing dialogue and regular communication. Conclusions: PPIE can enhance the quality and depth of doctoral research, as lived experiences shared by PPIE members add to research's components. Exposing early‐career researchers to PPIE can build research cultures sensitive to PPIE's potential contribution and develop the expertise needed to avoid tokenistic involvement. Capturing lay perspectives is essential in mental health research to ensure research findings are accessible and that findings inform clinical practice. However, clear guidance on the ethical dimensions to PPIE is needed.